Central flows to panchayats: a comparative study of Madhya Pradesh - Rao, C. Bhujana; Jena, Pratap Ranjan; Gupta, Manish (2007)
Central flows to panchayati raj institutions consist of assistance through centrally sponsored schemes, and transfers based on recommendation of Central Finance Commissions. The CSS are of two types, one routed through state government budgets, and the other bypassing state budgets. The paper quantifies these and identifies the components of the second going to panchayati raj institutions. For Madhya Pradesh and other major states, the paper provides per capita estimates of CSS releases to the PRIs for 2004-05 and 2005-06. - Reproduced.
Keywords: Panchayat - India - Madhya Pradesh; Panchayat